Slope Stability Assessment Using Limit Equilibrium Method With Deterministic and Probabilistic Approach (Case Study : Mota’ain-Motamasin National Road, East Nusa Tenggara, Indonesia - Zakki, Muhammad; Soemitro, Ria Asih Aryani; Satrya, Trihanyndio Rendy; Fitra, Andria Muharami (Journal of Infrastructure & Facility Asset Management, 2023)
The Mota'ain-Motamasin road section is a road section that was built in the realization of infrastructure development in the border area in East Nusa Tenggara which borders Timor Leste. On this section, road construction has been completed, but at several points there are landslides that need to be addressed. Research conducted includes modeling and testing in the laboratory. Physical, mechanical, suction and XRD tests were carried out on the samples. Back analysis was carried out to obtain soil parameters during landslides. Then analyzed the stability of the slopes Sta 149+140 with deterministically and probabilistically and analyzed the sensitivity of soil parameters to the value of Safety Factor. Bobonaro soil is classified as Cohesive Soil and has a value of    Liquid Limit = 80.823% and Plasticity Index value = 58.747%, classified as CH (High Plasticity Clay) soil. Bobonaro soil has kaolinite content of 3.4%-17.9%, illite 16.6%-42.6%, and montmorillonite 9.6%-30.6%. The combination of small amount of kaolinite and high montmorillonite accompanied by high changes in water content is the cause of frequent landslides on the mota'ain-motamasin roads. At Sta 149+140, the value of Safety Factor = 1,249 at GWT 0 m becomes SF = 1,254 at GWT -5 m probabilistically 10,000 iterations. The value of SF = 1,254 without suction becomes SF = 1,263 when there is suction at GWT -5 m probabilistically 10,000 iterations. The most sensitive soil parameter on the Safety Factor is cohesion, followed by the internal shear angle and unit weight. Handling of Sta 149+140 landslides used bore piles with SF=1.808 > SF=1.5.